Development of Learning Media using Google Maps Application and Here Wego Application to Improve Spatial Thinking Ability in Students at SHS 6 Pinggir - Safina, Laila; Suasti, Yurni; Ernawati, Ernawati (International Journal of Educational Dynamics, 2021)
Students participate in the Teaching and Learning Process (TLP) passively, resulting in a lack of development of their creative power in learning. The learning process that occurs in the classroom becomes meaningless. Even though learning will be more meaningful if students experience what they learn, not just know it, educators try to make what students learn at school useful in everyday life. The ability to think spatially is the ability to recognize space and is a strong focus in geography education. Students' ability to think spatially can help them understand the essence of geography material. The research method used in this research is a descriptive method with a quantitative approach. This research is part of the research on the development of a spatial thinking ability test instrument. Based on the results of hypothesis testing using the t-test at a significant level of 0.05, That is, there is no significant difference in student learning outcomes between the learning process using the Google Maps application learning media and the application Here We Go on improving spatial thinking skills at SHS 6 Pinggir. The results of these calculations show that the use of Google Maps and Here We Go application learning media in geography learning has a positive impact on improving spatial thinking skills.